A cadmium sulfide quantum dot-silica gel composite material and its preparation method and application

By forming high-photosensitive and photocorrosive-resistant cadmium sulfide quantum dot-silica gel composite on the silica gel support, combined with Rh complex, the instability problem of cadmium sulfide photocatalyst in the photocatalytic process is solved, and high efficiency is achieved Coenzyme NADH regeneration and recycling.

CN116116435BActive Publication Date: 2024-12-27ZUNYI MEDICAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310200086.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-02
Publication Date
2024-12-27
Estimated Expiration
2043-03-02

AI Technical Summary

Technical Problem

The existing cadmium sulfide (CdS) photocatalysts have the recombination problems of photogenerating electrons and holes and photocorrosion problems during photocatalysis, which leads to instability and difficulty in recycling, limiting their application in coenzyme NADH regeneration.

Method used

Silicone is used as a support and adsorbs Cd2+ and S2- by ball milling to form a high photosensitive and photocorrosive cadmium sulfide quantum dot-silica gel composite (CdS QDs-S) and combine it with Rh complex to enhance the photocatalyst. performance.

Benefits of technology

The photosensitive and recycle times of photocatalysts are significantly improved, the regeneration efficiency of coenzyme NADH is improved, the life of the photocatalyst is extended, and the recombination rate of photogenerated electrons and holes is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116116435B_ABST
    Figure CN116116435B_ABST
Patent Text Reader

Abstract

The present application discloses a preparation method of a cadmium sulfide quantum dot-silica gel composite material in the field of photocatalyst preparation technology. The method combines continuous ion adsorption and ball milling to successfully form CdS QDs on the surface of silica gel. In the composite material, silica gel is used as a carrier. The surface of silica gel is rich in ‑OH and Cd 2+ , Rh 2+ Metal ions have affinity and can effectively adsorb Cd 2+ It promotes the generation of CdS QDs and the energy transfer between the photocatalyst and the Rh complex, improving the regeneration performance of photocatalytic NADH. And through the mechanical force of ball milling, the CdS QDs are evenly dispersed and embedded on the surface of silica gel, and a highly photosensitized CdS QDs-S composite material is obtained, whose photosensitivity is 31 times that of pure CdS. Silica gel as a shielding agent improves the problem of CdS QDs being corroded by light and improves the recycling performance of the CdS QDs-S composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalyst preparation, and in particular to a cadmium sulfide quantum dot-silica gel composite material and a preparation method and application thereof. Background Art

[0002] Bioenzyme catalysis is widely used in the chemical and pharmaceutical industries due to its advantages such as high stereoselectivity, mild reaction conditions and few by-products. Among them, oxidoreductases are a widely used class of enzymes, accounting for about a quarter of all known enzymes. However, most oxidoreductases require the participation of coenzymes / cofactors NAD(P)H in the catalytic process to provide hydrogen and electrons. The coenzymes are also consumed in a stoichiometric ratio (i.e., one molecule of coenzyme is consumed for each molecule of substrate catalyzed) and have high external costs, which limits the application of oxidoreductases. Therefore, it is particularly important to construct an efficient coenzyme regeneration system to promote the enzymatic hydrogenation process. The coenzyme regeneration methods reported so far are mainly enzymatic, chemical, electrochemical, and photochemical methods. Among these methods, the photochemical method uses clean and renewable light energy, has mild reactions, can be designed paths, and has easy-to-analyze mechanisms, making photocatalysis show unique potential in cofactor regeneration.

[0003] The driving mechanism of photocatalytic NADH coenzyme regeneration is inspired by photosynthesis. After absorbing light, the photocatalyst generates photogenerated electron-hole pairs. The electrons are excited to the conduction band and migrate from the photocatalyst matrix to the surface. The electrons on the surface of the photocatalyst are transported by the Rh complex, transferring two electrons and one of their own protons to NAD+, and NAD+ generates NADH. The holes left in the valence band will also recombine with the electrons to a certain extent. In order to inhibit the recombination of electrons and holes, electron donors (triethanolamine, disodium ethylenediaminetetraacetic acid, etc.) are added to neutralize the holes. The key to the photocatalytic regeneration of the coenzyme NADH lies in high-performance photocatalysts, that is, high photosensitivity, wide visible light response range, and directional transmission of photogenerated carriers to reduce the recombination rate of photogenerated electrons and holes. CdS has been widely used in the field of photocatalysis due to its strong visible light absorption ability, suitable band gap (~2.4eV) and more negative conduction band edge. However, in all the reported works, CdS photocatalytic materials still have two inherent problems: (1) the recombination of photogenerated electrons and holes; (2) the photocorrosion problem, i.e., the S in CdS 2- It is easily oxidized by photogenerated holes, accompanied by toxic cadmium ions Cd 2+ This makes CdS very unstable and not conducive to recycling and large-scale application. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention designs a cadmium sulfide quantum dot-silica gel composite material (CdS QDs-S) with high photosensitivity and photocorrosion resistance, and applies the CdS QDs-S to the efficient regeneration of photocatalytic NADH.

[0005] One of the purposes of the present invention is to provide a method for preparing a cadmium sulfide quantum dot-silica gel composite material with high photosensitivity and light corrosion resistance, comprising the following steps: placing silica gel in a ball milling jar, firstly adsorbing Cd in a Cd-containing solution by ball milling 2+ , and then adsorb S in the sulfide salt solution 2- , CdS QDs are formed on the surface of silica gel, which are freeze-dried to obtain CdS QDs material with silica gel as a carrier.

[0006] As a preferred embodiment of the preparation method of the present invention, in the above preparation steps, the Cd-containing solution includes one of CdSO4 solution, CdCl2 solution or Cd(CH3COO)2·2H2O solution, preferably CdSO4 solution.

[0007] As a preferred embodiment of the preparation method of the present invention, in the above preparation steps, the sulfide salt solution includes one of Na2S solution, CH4N2S solution or C2H5NS solution, preferably Na2S solution.

[0008] The present invention adopts a method of using silica gel as a carrier to respectively adsorb Cd in CdSO4 by ball milling. 2+ and S in Na2S solution 2- , CdS QDs were successfully formed on the silica gel surface, denoted as CdS QDs-S.

[0009] More preferably, in the above synthesis step, the material of the ball mill is agate, and the ball milling conditions are: 15 agate beads with a diameter of 0.8 cm, 30 agate beads with a diameter of 0.5 cm, and a rotation speed of 500 rpm.

[0010] More preferably, the number of ball milling is 2 to 5 times, the single ball milling time is 10 to 30 minutes, preferably 20 minutes, the centrifugal condition is 9000rpm for 5 minutes, and after the last adsorption, it is washed three times with deionized water to wash away the excess S 2- , and finally vacuum freeze-dried.

[0011] More preferably, the freeze-drying conditions are 5 Pa, -60°C.

[0012] The second object of the present invention is to provide a cadmium sulfide quantum dot-silica gel composite material (CdS QDs-S) prepared by the above method and having high photosensitivity and anti-photocorrosion performance.

[0013] The present invention synthesizes a cadmium sulfide quantum dot-silica gel (CdS QDs-S) composite material, using silica gel as a carrier, and its surface is rich in -OH and Cd 2+ , Rh 2+ Metal ions have affinity and can effectively adsorb Cd 2+ It promotes the generation of CdS QDs and the energy transfer between the photocatalyst and the Rh complex, improving the regeneration performance of photocatalytic NADH. Through the mechanical force of ball milling, CdS QDs are evenly dispersed and embedded on the surface of silica gel, and a highly photosensitized CdS QDs-S composite material is obtained, whose photosensitivity is 31 times that of pure CdS. Silica gel as a shielding agent improves the problem of CdS QDs being corroded by light and improves the recycling performance of the CdS QDs-S composite material.

[0014] The third object of the present invention is to provide the use of the above composite material (CdS QDs-S) as a photocatalyst in the regeneration of coenzyme NADH.

[0015] The CdS QDs-S photocatalyst is applied in the regeneration of coenzyme NADH, and the application comprises the following steps:

[0016] (1) The composite material is combined with the coenzyme NAD + , electron donor, and Rh complex in a quartz test tube to obtain a mixture A;

[0017] (2) Place mixture A in a photoreactor, stir in the dark for 10 min, use 420 nm blue light as the light source, at a temperature of 25° C. to 30° C., 0.1 M PB, pH = 6.0, and react to obtain NADH.

[0018] Preferably, the mixture A is stirred in the dark for 10 min to reach adsorption-desorption equilibrium, and then a blank sample is obtained, and then samples are taken every 4 min until the fifth sample is taken; after the sample is diluted 20 times, the photocatalyst in the reaction solution is filtered with a 0.22 μm filter membrane, and the extinction coefficient of NADH at 340 nm in an ultraviolet spectrophotometer is 6220 M -1 cm -1 Obtain NADH yield.

[0019] More preferably, the CdS QDs-S photocatalyst of the present invention can achieve a NADH reproduction rate of about 60% to 70% within 20 minutes when used for the regeneration of the coenzyme NADH.

[0020] More preferably, the electron donor in step (1) is EDTA-4Na, the Rh complex is [Cp*Rh(bpy)(H2O)]2; the ratio of the components in the mixture A is: CdS QDs-S: coenzyme NAD +:EDTA-4Na:Rh complex=10mg:1mmol:20w / v%:0.25mmol.

[0021] More preferably, the light source in step (2) is 1.5A, 12W, 420nm blue light, the rotation speed is 40rpm, the temperature is 25°C, and the pH value is 0.1M=6.0PB.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The photocatalyst CdS QDs-S is synthesized by continuous ion adsorption and ball milling. The continuous ion adsorption method can adsorb CdS on the silica gel carrier in the form of quantum dots. In terms of adsorption, the ball milling method can make the CdS quantum dots evenly dispersed and embedded on the surface of silica gel, preventing it from being corroded by light and extending the number of cycles of CdS QDs-S.

[0024] 2. Silica gel is used as a carrier, and its surface is rich in -OH and Cd 2+ , Rh 2+ Metal ions have affinity, which can accelerate the efficiency of electron transfer and thus improve the regeneration efficiency of photocatalytic NADH.

[0025] 3. The photosensitivity of the photocatalyst CdS QDs-S is 31 times that of pure CdS, indicating the enrichment of electrons on the surface of CdS QDs-S. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 XRD patterns of pure CdS, silica gel and CdS QDs-S composites with different contents.

[0027] Figure 2 are SEM images of silica gel and CdS QDs-S5, respectively.

[0028] Figure 3 The EDS mapping element analysis diagram obtained by SEM. ae, the table in each figure corresponds to the CdS QDs content in the composite materials of CdS-QDs-S1, CdS-QDs-S2, CdS-QDs-S3, CdS-QDs-S4, and CdS-QDs-S5.

[0029] Figure 4 HRTEM images of silica gel and CdS QDs-S5.

[0030] Figure 5 a is the SEM image of pure CdS, and b is the HRTEM analysis image.

[0031] Figure 6FTIR images of silica gel, pure CdS and CdS QDs-S composites with different contents.

[0032] Figure 7 XPS graphs of silica gel, pure CdS, CdS QDs-S1 and CdS QDs-S5.

[0033] Figure 8 Figures a and b are the XPS valence band spectra of pure CdS, CdS QDs-S1 and CdS QDs-S5; Figures c and d are the UV-visible diffuse reflectance spectra and tauc plots of pure CdS, CdS QDs-S1 and CdS QDs-S5, respectively.

[0034] Fig. 9 a and b are PL spectra of silica gel, pure CdS, CdS QDs-S1 and CdS QDs-S5; c and d are chronoamperometry and EIS diagrams of pure CdS and CdS QDs-S1, respectively.

[0035] Fig.10 a is the photocatalytic NADH regeneration kinetics of CdS QDs-S2 synthesized at different ball milling times; b is the photocatalytic NADH regeneration kinetics of different electron donors; c is the photocatalytic NADH regeneration kinetics of different concentrations of EDTA-4NA; d is the photocatalytic NADH regeneration kinetics of different concentrations of Rh complexes.

[0036] Fig.11 It shows the photocatalytic NADH regeneration kinetics when the electron donors are TEOA and EDTA-4Na.

[0037] Fig.12 Figure a is a kinetic diagram of photocatalytic NADH regeneration using 0.1M PB solution at different pH values; Figure b is a kinetic diagram of photocatalytic NADH regeneration using different reaction temperatures; Figure c is a kinetic diagram of photocatalytic NADH regeneration using different CdS QDs-S2 dosages; and Figure d is a kinetic diagram of photocatalytic NADH regeneration using different NAD+ concentrations.

[0038] Fig.13 (a) is the kinetic diagram of photocatalytic NADH regeneration of pure CdS and CdS QDs-S composites with different loading amounts; (b) is the photocatalytic NADH reproduction efficiency of pure CdS and CdS QDs-S composites with different loading amounts; (c) and (d) are the monitoring diagrams of NADH concentration changes in photocatalytic NADH regeneration of CdSQDs-S2 and pure CdS.

[0039] Fig.14a is a cyclic reaction diagram of pure CdS and CdS QDs-S composites with different loading amounts in photocatalytic NADH regeneration; b and c are HRTEM images of pure CdS and CdS QDs-S5 after photocatalytic NADH regeneration reaction cycles, respectively.

[0040] Fig.15 a is the standard curve of benzyl alcohol; b is the photocatalytic NADH regeneration ADH enzyme coupling reaction and blank experiment using pure CdS and CdS QDs-S as photocatalysts. DETAILED DESCRIPTION

[0041] The following is further described in detail through specific implementation methods:

[0042] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific examples. The reagents used in the following examples can all be purchased from commercial channels.

[0043] Example 1

[0044] As a method for preparing a CdS QDs photocatalyst according to an embodiment of the present invention, the method comprises the following steps: according to the theoretical loading amount of cadmium sulfide of 10%, 20%, 40%, 60%, and 80%, respectively, 1.4448g, 1.4448g, 1.0836g, 0.9632g, 0.7224g of silica gel, 10ml, 20ml, 30ml, 40ml, 40ml of 0.1M CdSO4 / Na2S, 15 agate beads with a diameter of 0.8cm and 30 agate beads with a diameter of 0.5cm are added to an agate ball mill, and 0.1M CdSO4 solution is first added to adsorb Cd 2+ , then add 0.1M Na2S solution to absorb S 2- , a total of 4 adsorptions, each adsorption ball milling condition is 500rpm, single ball milling time is 20min, a total of 4 ball milling adsorptions, each ball milling is centrifuged at the end of the centrifugation, the centrifugation condition is 9000rpm, 5min, after the last adsorption, it is washed three times with deionized water to wash away the excess S 2- , and finally vacuum freeze-dried at 5Pa, -60°C. The actual CdS loadings obtained from EDS mapping results were 1.77wt%, 3.94wt%, 7.65wt%, 9.34wt%, and 21.31wt%, which were respectively recorded as CdS QDs-S1, CdS QDs-S2, CdS QDs-S3, CdS QDs-S4, and CdS QDs-S5.

[0045] The CdSO4 solution was replaced by a CdCl2 solution or a Cd(CH3COO)2·2H2O solution; the sulfide salt solution was replaced by a CH4N2S solution or a C2H5NS solution, and cadmium sulfide quantum dot-silica gel composite materials with different contents were prepared according to the method of Example 1.

[0046] The CdS QDs-S2 prepared in this example was used to screen the ball milling time. Specifically, 1.4448 g of silica gel, 20 ml of 0.1 M CdSO4 / Na2S, 15 agate beads with a diameter of 0.8 cm, and 30 agate beads with a diameter of 0.5 cm were added to the agate ball mill. 0.1 M CdSO4 solution was first added to adsorb Cd 2+ , then add 0.1M NaS solution to absorb S 2- , a total of 4 adsorptions, each adsorption ball milling condition is 500rpm, the single ball milling time is 20min, 40min, 60min, 80min and 100min, a total of 4 ball milling adsorptions, each ball milling is centrifuged at the end of the centrifugation, the centrifugation condition is 9000rpm, 5min, after the last adsorption, it is washed three times with deionized water to wash away the excess S 2- , and finally vacuum freeze-dried at 5Pa, -60℃.

[0047] The photocatalysts obtained in the above steps were recorded as CdS QDs-S2-20 min, CdS QDs-S2-40 min, CdS QDs-S2-60 min, CdS QDs-S2-80 min and CdS QDs-S2-100 min and used for photocatalytic NADH regeneration reaction, specifically, 12W1.5 A 420nm blue light was used as the light source, the photocatalysts CdS QDs-S2-20 min, CdS QDs-S2-40 min, CdS QDs-S2-60 min, CdS QDs-S2-80 min and CdS QDs-S2-100 min were 10 mg, and the coenzyme NAD + 1mM and 0.25mM Rh complexes were added to 0.1M PB solution with pH 9.0 containing 15w / v% TEOA electron donor (a total of 10ml system), stirred in the dark for 10min at room temperature, and then a blank sample was taken. After that, a sample was taken every 4min of illumination, and the process ended after the fifth sample. The sample was diluted 20 times and filtered through a membrane (0.22um) to measure its absorbance at 340nm. The extinction coefficient of NADH at 340nm in a UV spectrophotometer was 6220M-1cm -1 Obtain NADH yield.

[0048] The CdS QDs-S2-20 min, CdS QDs-S2-40 min, CdS QDs-S2-60 min, CdSQDs-S2-80 min and CdS QDs-S2-100 min photocatalysts prepared above were subjected to NADH regeneration reaction, such as Fig.10 As shown in a, the yields of NADH were 65.6%, 63.7%, 64.0%, 63.7% and 62.7%, respectively, and CdS QDs-S2-20min was finally selected.

[0049] See the attached drawings: Figure 1 Three broad diffraction peaks at 26.7°, 44.2°, and 52.1° are shown for pure CdS, silica gel, and CdS QDs-S composites with different contents, which correspond to the diffraction patterns of the CdS cubic crystal structure (PDF#01-080-0019), and no CdS diffraction peaks are observed in the pure silica gel sample. Figure 2 ab are SEM images of silica gel and CdS QDs-S5, respectively. It can be seen that there are many mesopores on the surface of silica gel, which is conducive to the embedding of CdS QDs. Compared with CdS, the CdS QDs in CdS QDs-S5 are evenly dispersed or embedded on the surface of silica gel. Figure 3 aeIn order to determine the CdS content of different CdS QDs-S materials, EDS mapping analysis showed that the CdS contents of photocatalysts CdS QDs-S1, CdS QDs-S2, CdS QDs-S3, CdS QDs-S4 and CdSQDs-S5 were 0.93wt%, 3.43wt%, 7.32wt%, 8.74wt% and 21.24wt%, respectively. Figure 4 a is a high-resolution transmission electron microscopy image and selected area electron diffraction image of silica gel. It can be observed that the surface of silica gel has an amorphous structure, and no crystal information is observed. Figure 4 bf are the crystal structure, grain size, crystal plane angle and lattice spacing of CdS QDs in CdS QDs-S5 composite materials. Figure 5 ae are the SEM and HRTEM images of pure CdS, respectively, as well as the size, exposed crystal planes, and lattice spacing of the nanoparticles obtained by further analysis. Figure 6 Figure 2 shows the FTIR images of silica gel, pure CdS and CdS QDs-S composites with different contents. The CdS QDs-S composites show absorption bands similar to those of silica gel. Specifically, ~3450cm -1 The broad absorption band at 1638cm is the stretching vibration peak of -OH; -1 The peak near is the bending vibration peak of HOH; 1095cm -1The strong broad absorption band at 955cm is the stretching vibration peak of Si-O-Si. -1 The absorption peak at 798 cm is the bending vibration peak of Si-OH. -1 and 466cm -1 The absorption peak at is the stretching vibration peak of the Si-O bond. Due to the low content of CdS, no absorption peak of CdS was detected in the FTIR graph, and no new chemical bonds were detected. This shows that there is no chemical reaction between silica gel and CdS QDs. The valence states of Si, O, Cd, and S in silica gel, CdS, and CdS-QDs-S composites were analyzed by XPS spectroscopy. Figure 7 The results show that the valence states of Cd and S in CdS QDs-S1 and CdS QDs-S5 samples have not changed compared with pure CdS, and the valence states of Si and O have not shifted compared with silica gel. It can be confirmed that there is no chemical interaction between CdS QDs and silica gel carrier.

[0050] Photoelectric performance analysis

[0051] Figure 8 ab are XPS valence band spectra, which show that the valence bands of CdS QDs-S1 and CdS QDs-S5 composite materials are 1.13 eV and 0.92 eV, respectively. Compared with pure CdS, pure CdS has a more positive valence band (1.66 eV), that is, a stronger oxidation ability. Figure 8 cd, respectively, are UV-Vis diffuse reflectance spectra and the tauc plots extended therefrom. The light absorption edge of pure CdS (571nm) is greater than the light absorption edge of CdS QDs-S1 and CdS QDs-S5 composites (548-551nm). This is because silica gel is non-photosensitive and some CdS QDs are embedded in the surface of silica gel, which has a slight effect on the light absorption capacity of CdS QDs-S composites. The tauc plot shows that the band gaps of CdS QDs-S1, CdS QDs-S5 composites and pure CdS are 2.26eV, 2.23eV and 2.16eV, respectively, which is consistent with the results of UV-Vis diffuse reflectance spectra. The conduction band values ​​are further calculated by combining the valence band and the band gap. The conduction bands of CdS QDs-S1, CdS QDs-S5 composites and pure CdS are -1.13eV, -1.41eV and -0.5eV, respectively. According to the conduction band value, the CdS QDs-S composite material has a more negative conduction band edge, that is, a stronger reduction ability. This may be because the -OH on the surface of silica gel as a carrier can promote the transfer of electrons and improve the utilization rate of electrons. Fig. 9As shown in ab, the photoluminescence (PL) spectra of silica gel, pure CdS, CdS QDs-S1 and CdS QDs-S5 were characterized. The results show that the silica gel sample has no photosensitivity, but two signal peaks can be observed on the PL signal of pure CdS, CdS QDs-S1 and CdS QDs-S5 samples. It is worth noting that the CdS QDs-S5 sample has stronger photosensitivity than pure CdS, which is 31 times that of pure CdS. Fig. 9 c. Pure CdS and CdS QDs-S5 were coated on the working electrode respectively, and the chronoamperometric test was carried out under the same conditions. For comparison, the tests were carried out in the dark and after 20 minutes of illumination. The results showed that CdS QDs-S5 showed stronger electron transfer efficiency in the dark, and the current generated was 214μA, while that of pure CdS was 180μA. Under illumination, the generation of photogenerated electrons increased the intensity of the current. The current of the CdS QDs-S5 composite material was 270μA, and that of pure CdS was 240μA. Fig. 9 d Combined with EIS test of electron transfer resistance, the impedance curve radius of CdS QDs-S5 composite material is significantly smaller than that of pure CdS, confirming that CdS QDs-S5 composite material has smaller electron transfer resistance.

[0052] Example 2

[0053] The CdS QDs-S2-20 min in Example 1 was used for electron donor screening and was subjected to NADH regeneration reaction under the conditions of 15 w / v% TEOA, L-ascorbic acid, CH3OH, EDTA-4Na, EDTA, and EDTA-2Na electron donors. The other reaction conditions were the same as those in Example 1 except that the electron donors were different. Fig.10 As shown in b, the yields of NADH were 65.6%, 0%, 0%, 65.6%, 1.8% and 4.8%, respectively.

[0054] Example 3

[0055] EDTA-4Na and TEOA were used as electron donors and the reaction conditions were the same as in Example 2. Fig.11 By extending the reaction time, it was found that NADH regenerated by EDTA-4Na as an electron donor was more stable. Finally, EDTA-4Na was selected as the electron donor.

[0056] Example 4

[0057] The CdS QDs-S2-20 min in Example 1 was used to screen the amount of EDTA-4Na. The NADH regeneration reaction was performed under the conditions of 5 w / v%, 10 w / v%, 15 w / v%, 20 w / v%, 25 w / v%, and 30 w / v% of the EDTA-4Na electron donor. Except for the different amounts of electron donors, other reaction conditions were the same as those in Example 1. Fig.10 As shown in Figure c, the yields of NADH were 21.5%, 55.6%, 59.2%, 65.3%, 65.0% and 68.8%, respectively, and 20w / v% EDTA-4Na was finally selected.

[0058] Example 5

[0059] The CdS QDs-S2-20 min in Example 1 was used to screen the amount of Rh complex. The amounts of Rh complex were 0.1 mM, 0.15 mM, 0.2 mM, 0.25 mM, and 0.3 mM, respectively, for NADH regeneration reaction. Specifically, 12 W 1.5 A 420 nm blue light was used as the light source, the photocatalyst CdS QDs-S2-20 min was 10 mg, and the coenzyme NAD + 1mM was added to a PB solution containing 20w / v% EDTA-4Na electron donor 0.1M pH 9.0 (a total of 10ml system), stirred in the dark at room temperature for 10min, and then a blank sample was taken. After that, a sample was taken every 4min of illumination, and the process ended after the fifth sample. The sample was diluted 20 times and filtered through a membrane (0.22um) to measure its absorbance at 340nm. The extinction coefficient of NADH at 340nm in a UV-Vis spectrophotometer was 6220M -1 cm -1 The NADH yield is obtained. Fig.10 As shown in Figure d, the yields of NADH were 62.1%, 62.4%, 63.7%, 65.0%, 65.0% and 64.3%, respectively, and 0.25 mM Rh complex was finally selected.

[0060] Example 6

[0061] The CdS QDs-S2-20 min in Example 1 was used for pH screening, and the photocatalytic NADH regeneration reaction was carried out at pH = 5.0, pH = 6.0, pH = 7.0, pH = 8.0, and pH = 9.0, respectively. Except for the Rh complex dosage of 0.25 mM and the reaction pH, the other reaction conditions were the same as those in Example 5. Fig.12 As shown in a, the yields of NADH were 65.3%, 65.0%, 62.7%, 61.7% and 61.4%, respectively, and PB with pH = 6.0 was finally selected.

[0062] Example 7

[0063] The CdS QDs-S2-20 min in Example 1 was used for the screening of reaction temperature, and the photocatalytic NADH regeneration reaction was carried out at 5°C, 10°C, 15°C, 20°C, and 25°C, respectively. Specifically, 12W1.5A 420nm blue light was used as the light source, the photocatalyst CdSQDs-S2-20min was 10mg, the coenzyme NAD + 1mM was added to a PB solution containing 20w / v% EDTA-4Na electron donor 0.1M pH 6.0 (a total of 10ml system), stirred in the dark at room temperature for 10min, and then a blank sample was taken. After that, a sample was taken every 4min of illumination, and the process ended after the fifth sample. The sample was diluted 20 times and filtered through a membrane (0.22μm) to measure its absorbance at 340nm. The extinction coefficient of NADH at 340nm in a UV-Vis spectrophotometer was 6220M -1 cm -1 The NADH yield is obtained. Fig.12 As shown in b, the yields of NADH were 60.8%, 67.2%, 60.8%, 61.7%, 65.0% and 65.0%, respectively, and the final reaction temperature was 25°C.

[0064] Example 8

[0065] The CdS QDs-S2-20min in Example 1 was used to screen the amount of photocatalyst, and 10 mg, 20 mg, 30 mg, 40 mg, and 50 mg of CdS QDs-S2-20min were used for photocatalytic NADH regeneration reaction, respectively. Except for the reaction temperature of 25°C and the different amounts of photocatalyst, the other reaction conditions were the same as those in Example 7. Fig.12 As shown in c, the yields of NADH were 63.3%, 55.9%, 55.6%, 54% and 55%, respectively, and finally 10 mg of the photocatalyst was selected.

[0066] Example 9

[0067] The CdS QDs-S2-20min in Example 1 was used for NAD + Screening of dosage, using 1mM, 3mM, 5mM, 10mM, 20mM NAD + For photocatalytic NADH regeneration reaction, in addition to the photocatalyst dosage of 10 mg and NAD + The other reaction conditions are the same as those in Example 8 except for the amount used. Fig.12 As shown in d, the yields of NADH were 60.1%, 57.8%, 52.7%, 38.2%, and 19.6%, respectively. Finally, 1 mM NAD + .

[0068] Example 10

[0069] The photocatalysts CdS, CdS QDs-S1, CdS QDs-S2, CdS QDs-S3, CdS QDs-S4 and CdS QDs-S5 in Example 1 were used for photocatalytic NADH regeneration reaction, specifically using 12W 1.5A 420nm blue light as the light source, 10mg of photocatalyst, and coenzyme NAD + 1mM and 0.25Mm Rh complexes were added to a PB solution containing 20w / v% EDTA-4Na electron donor 0.1M pH 6.0 (a total of 10ml system), stirred in the dark at room temperature for 10min, and then a blank sample was taken. After that, a sample was taken every 4min of illumination, and the process ended after the fifth sample. The sample was diluted 20 times and filtered through a membrane (0.22um) to measure its absorbance at 340nm. The extinction coefficient of NADH at 340nm in a UV spectrophotometer was 6220M. -1 cm -1 The NADH yield is obtained. Fig.13 As shown in ab, the yields of NADH were 49.2%, 68.8%, 64.0%, 67.5%, 68.8% and 65.0%, respectively. Fig.13 cd is CdS QDs-S2 and CdS as photocatalysts in the NADH regeneration reaction, and the changes in NADH regeneration concentration are monitored by UV-Vis spectrophotometer.

[0070] Embodiment 11

[0071] The photocatalysts CdS, CdS QDs-S1, CdS QDs-S2, CdS QDs-S3, CdS QDs-S4 and CdS QDs-S5 in Example 1 were used for photocatalytic NADH regeneration cycle reaction, specifically using 12W 1.5 A 420nm blue light as the light source, 20 mg of photocatalyst, and coenzyme NAD + 1mM and 0.25mM Rh complexes were added to a PB solution containing 20w / v% EDTA-4Na electron donor 0.1M pH 6.0 (a total of 10ml system), and a blank sample was taken after stirring in the dark for 10min at room temperature. After that, a sample was taken at a fixed reaction time. The sample was diluted 20 times and filtered through a membrane (0.22um) to measure its absorbance at 340nm. The extinction coefficient of NADH at 340nm in a UV-Vis spectrophotometer was 6220M. -1 cm -1 The NADH yield is obtained, and the reaction solution is centrifuged to recover the photocatalyst for the next reaction. Fig.14As shown in a, the photocatalysts CdS, CdS QDs-S1, CdS QDs-S2, CdS QDs-S3, CdS QDs-S4, and CdS QDs-S5 can be recycled 5, 4, 6, 9, 8, and 10 times, respectively, in the photocatalytic NADH regeneration reaction when the electron donor is EDTA-4Na. The amount of photocatalyst CdS used is 4.2 mg, which is the same as the content of CdS QDs in CdS QDs-S5. The recycling number of CdS QDs-S5 composite materials is twice that of CdS. Fig.14 b and c are the HRTEM images of pure CdS and CdS QDs-S5 after cyclic reaction, respectively. Pure CdS is photocorroded during the cyclic process and the CdS crystal structure is destroyed. However, the HRTEM image of CdS QDs-S5 after cyclic reaction shows that the CdS crystal structure is maintained.

[0072] Example 12

[0073] The photocatalyst CdS QDs-S5 in Example 1 was used to verify the biological activity of photocatalytically regenerating NADH, that is, whether the regenerated NADH is 1,4-NADH. The verification was carried out by coupling with ADH alcohol dehydrogenase to reduce benzaldehyde to benzyl alcohol. Specifically, 12W1.5 A420nm blue light was used as the light source, 20mg of photocatalyst, coenzyme NAD + 5mM and 0.25mM Rh complexes were added to a PB solution containing 20w / v% EDTA-4Na electron donor 0.1M pH 6.0 (a total of 10ml system), stirred in the dark for 10min at room temperature and then illuminated for 1h. The reaction solution was filtered with a 0.22μm filter membrane, and the NADH regeneration solution was stirred with 2mg / ml ADH and 1mM benzaldehyde in the dark for 24h, with a total of 5ml system. The yield of the final benzyl alcohol was determined by HPLC, as shown in Fig.15 As shown, the yield is 52.3%. In comparison, the same reaction was carried out using CdS, and the yield of benzyl alcohol was 56.6%, while the ADH enzyme-catalyzed reaction without NADH regeneration solution had a benzyl alcohol yield of 9.2%.

[0074] The above is only an embodiment of the present invention, and the common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing a cadmium sulfide quantum dot-silica gel composite material, characterized in that: The following steps are involved: Place silica gel in a ball mill and add Cd-containing solution to absorb Cd. 2+ , and then add sulfur source solution to absorb S 2- , adsorbed by ball milling to form CdS QDs on the surface of silica gel, the number of ball milling is 2 to 5 times, the single ball milling time is 10 to 30 min, centrifuged after each ball milling, the centrifugation condition is 9000 rpm, 5 min, washed three times with deionized water after the last adsorption, and finally freeze-dried to obtain a CdS QDs-S composite material with silica gel as the carrier; the sulfur source solution includes one of Na2S solution, CH4N2S solution or C2H5NS solution.

2. The preparation method according to claim 1, characterized in that: The Cd-containing solution includes one of a CdSO4 solution, a CdCl2 solution or a Cd(CH3COO)2·2H2O solution.

3. The preparation method according to claim 2, characterized in that: The freeze-drying conditions were 5 Pa, -60 °C.

4. The use of the cadmium sulfide quantum dot-silica gel composite material obtained by the preparation method according to claim 1 as a photocatalyst in the regeneration of coenzyme NADH, characterized in that: The following steps are involved: (1) 10 mg of CdS QDs-S composite material was mixed with 1 mM coenzyme NAD + , 20 w / v% electron donor EDTA-4Na, 0.25 mM Rh complex [Cp*Rh(bpy)(H2O)]2 in a quartz test tube to obtain mixture A; (2) Place mixture A in a photoreactor and stir in the dark for 10 min. Use 420 nm blue light as the light source, at a temperature of 25°C to 30°C, and 0.1 M PB at pH = 6.0 to produce NADH.

5. The use according to claim 4, characterized in that: The light source in step (2) is 1.5 A, 12 W, 420 nm blue light, the rotation speed is 40 rpm, the temperature is 25° C., and the pH of 0.1 M PB is 6.0.